Experimental study of a modified evaporative photovoltaic chimney including water sliding. (April 2019) - Lucas, M.; Ruiz, J.; Aguilar, F.J.; Cutillas, C.G.; Kaiser, A.S.; Vicente, P.G.
Abstract: Solar cooling provides an ideal coupling between solar energy and the need for cooling, since both reach their maximum during the summer. However, solar refrigeration technologies either have not been competitive or are in a preliminary stage of development. Photovoltaic (PV) driven compression chillers are the most promising and close to market solar solutions today in the case of small to medium units (¡50 kW cooling) due to the tremendous decrease in the cost of PV modules. The main objective of this work is to improve the efficiency of a PV panel by cooling it on its upper face by water sliding and on its back side using a solar chimney. In addition, the system is used as heat sink of a water chiller working as a low scale cooling tower. The work developed consisted of adapting and testing a prototype, changing its mode of operation to overcome the limitations encountered in the first campaign of measures. Several tests were performed by modifying the water mass flow rate circulated to the nozzles (spray) and onto the PV upper surface (water film). For the test with a water flow rate in nozzles of 500 l/h and sliding 250 l/h the results show an average cooling of the panel of 15°C and an improvement in the electrical efficiency of the panel of about 10%. The modified system is still able to dissipate a thermal power of about 1500 W with a thermal efficiency exceeding 30% in summer conditions. Highlights: The paper evaluates the thermal and electrical performance of a second version of a Photovoltaic Evaporative Chimney. An evaporative thermal efficiency exceeding 30% in summer conditions have been measured. An electrical efficiency improvement of 10% in a typical summer day.